Direct Regeneration in Cyclamen Persicum Mill. Using ‎Seedling Tissues - Hassan Abu-Qaoud (My University, 2004)
In Vitro shoot regeneration and microtuberization of Cyclamen persicum Mill. were studied using seedling tissues. Tuber, leaf and petiole sections of aseptic seedlings of cultivar ‘Concerto’ were established on Murashige and Skoog (MS) basal medium. Three levels of benzyladenine (BA) (4.4, 8.8, 13.3 µM) and four levels of thidiazuron (TDZ) (0.5, 1, 2, 4 µM) were used with the three different explants. All regeneration media were supplied with 5.4 µM naphthalene acetic acid (NAA). No shoot regeneration was observed in media without cytokinins. The greatest percent shoot regeneration (100 %) was obtained from tuber sections cultured on media supplemented with 4.4 µM BA and 4 µM TDZ. No regeneration was obtained with petiole sections. Microtubers were formed with leaf explant. The higher microtuberization response was obtained with leaf explants cultured on media supplemented with 2 and 4 µM TDZ (41.6 and 58.3, respectively). Tuberous structures (microtubers) were able to sprout and leaves continued to grow on these structures. After an acclimatization period, the plantlets were transferred to the greenhouse and continued their growth normally.